Comparison of parallel high-throughput RNA sequencing between knockout of TDP-43 and its overexpression reveals primarily nonreciprocal and nonoverlapping gene expression changes in the central nervous system of drosophila - Hazelett, D.J (2020)
10.1534/g3.112.002998